Seamless Indoor and Outdoor Location, Guidance and Visualization in Mobile Computing - Dias, J.; Calado. A.; Marcos., J. (Proceedings of Conference on Construction Applications of Virtual Reality 2005, CONVR 2005, Durham, 2005)
In this paper, we present the final version of our proposed system architecture for a global, fully mobile and location-based GIS system. This architecture has created an abstraction to support generic multi-level geo-referenced data, such as Earth Observation/Satellite Imagery, Remote Observation/Airborne Imagery, GIS Mapping and Mixed Reality. The architecture supports multiple modalities of presentation, visualization and interaction for each level of abstraction of georeferenced data, such as Image preview Scaled Vector Graphics preview, 3D visualization; and Augmented Reality visualization and interaction. The paper discusses and presents the results achieved with two Use Cases that have tested the proposed system architecture: one for Outdoor and another for Indoor Localization, Guidance and Visualization in urban areas, which can be seamlessly mixed together.